Finite Element Analysis and Statistical Method to Determine Temperature Distribution on Cutting Tool in End-Milling - K., Kadirgama; M. M., Noor; M. M., Rahman; W. S., Wan Harun (EuroJournals Publishing, Inc., 2009)

(untitled)
The aim of this study is to determine the temperature distribution on cutting tool when machining HASTELLOY C-22HS with carbide coated cutting tool. Response Surface Method (RSM) used to minimize the number of experiments and to develop first order temperature model. Finite element analysis (FEA) was used to verification of the temperature distribution on cutting tool. From FEA results show clearly that the relationship between the variables (cutting speed, feed rate and axial depth) with responses (temperature). From the first order model shows that cutting speed, feed rate and axial depth plays important role in producing cutting temperature. The feed rate has the most dominant parameter on the temperature, followed by the axial depth and cutting speed. The results from FEA were compared with the experimental values. The predicted values are quite close to the experimental results, even though its accuracy is slightly inferior as Finite Element Analysis and Statistical Method to Determine Temperature Distribution on Cutting Tool in End-Milling 452 compared to RSM. However, FEA is able to produce the temperature distribution around the cutting tool, in great detail.